2017
DOI: 10.1186/s13104-017-2594-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of Clostridium perfringens isolates from healthy and necrotic enteritis infected chickens and turkeys

Abstract: Objective Clostridium perfringens causes gastrointestinal diseases in both humans and domestic animals. Type A strains expressing the NetB toxin are the main cause of necrotic enteritis (NE) in chickens, which has remarkable impact on animal welfare and production economy in the international poultry industry. Three pathogenicity loci NELoc-1, -2 and -3 and a collagen adhesion gene cnaA have been found to be associated with NE in chickens, whereas the presence of these has not been investigated in diseased tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Adhesin is an important virulence factor in broiler-linked NE [14, 18], and in this study we found that adhesin genes (at least one variant) were overall enriched (P<0.0001) in NE-linked isolates (58/62; 93.5%) vs healthy isolates (9/20; 45%). Among all related adhesin variants, cna, cnaA and cnaD genes were significantly enriched in NE-associated C. perfringens isolates (P<0.05), linking these genes to NE-disease development (Additional file 2: Fig.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Adhesin is an important virulence factor in broiler-linked NE [14, 18], and in this study we found that adhesin genes (at least one variant) were overall enriched (P<0.0001) in NE-linked isolates (58/62; 93.5%) vs healthy isolates (9/20; 45%). Among all related adhesin variants, cna, cnaA and cnaD genes were significantly enriched in NE-associated C. perfringens isolates (P<0.05), linking these genes to NE-disease development (Additional file 2: Fig.…”
Section: Resultssupporting
confidence: 51%
“…At present there are only two smaller scale WGS-based studies on broiler-associated C. perfringens [14, 18]. Thus, to further our understanding on C. perfringens dissemination and virulence profiles in the context of broiler-NE, we performed phylogenetics and in-depth comparative genomics on 88 chicken-associated C. perfringens isolates, (strains from public genome databases, alongside 22 newly isolated and sequenced strains).…”
Section: Introductionmentioning
confidence: 99%
“…Birds raised on litter as was the case in the present study, are more likely to be colonized than birds reared on a wire floor. As long as our knowledge about the prevalence of virulent environmental turkey Clostridium perfringens strains is insufficient [15,16], a role of environmental Clostridium perfringens strains in lesion induction cannot be ruled out.…”
Section: Colonization Of the Small Intestine By Environmentalmentioning
confidence: 99%
“…The causative agent [1,2], pathogenesis [3,4], role of host immunity [5] and intestinal microbiota [6,7], epidemiology [8,9] and experimental reproduction [10] of this disease in broiler chickens have been extensively investigated. Necrotic enteritis occurs in turkeys and Clostridium perfringens has been implicated in the aetiology [11][12][13][14][15], but little information exists concerning the pathogenesis [16], immunity, microbiota or experimental reproduction of turkey necrotic enteritis.…”
Section: Introductionmentioning
confidence: 99%
“…This potent pore-forming toxin is reported to disrupt intestinal tight junction barriers, which is associated with intestinal disease symptoms (19). C. perfringens , and associated encoded toxins, have been extensively studied with respect to disease pathogenesis, with a strong focus on animal infections (2024). Recent studies analysing a range of diverse C. perfringens strains (from both animal and human-associated infections) indicates a plastic and divergent pangenome, with a significant proportion of accessory genes predicted to be involved in virulence mechanisms and metabolisms, linked to enhanced host colonisation and disease initiation (3, 25).…”
Section: Introductionmentioning
confidence: 99%